(untitled) (Journal of Oriental Studies, 2016)
Мақалада автор Ф.С. Фитцджеральд және Акрам Айисли шығармашылығындағы руханият мәселелеріне тоқталған. Article is devoted to the problem of spirituality, moral searches in creativity of F.S.Fitzgerald and Akram Aylisli. The author of article investigates characters of heroes, reveals the lines defining characteristic features of F.S.Fitzgerald’s and Akram Aylisli’s creativity. Common features and distinctions in creativity of both authors come to light.